2009
DOI: 10.1073/pnas.0903620106
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive control in media multitaskers

Abstract: Chronic media multitasking is quickly becoming ubiquitous, although processing multiple incoming streams of information is considered a challenge for human cognition. A series of experiments addressed whether there are systematic differences in information processing styles between chronically heavy and light media multitaskers. A trait media multitasking index was developed to identify groups of heavy and light media multitaskers. These two groups were then compared along established cognitive control dimensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

81
1,307
34
56

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 1,245 publications
(1,478 citation statements)
references
References 26 publications
81
1,307
34
56
Order By: Relevance
“…This finding is broadly consistent with a growing body of research, using more general media multitasking questionnaires, that shows that higher endorsement of media multitasking habits is associated with lower performance of computerized attention tasks (e.g., Cain et al, 2016;Moisala et al, 2016;Ophir et al, 2009). As well, students who endorse more frequent media multitasking-particularly in academic contexts-show poorer academic performance (e.g., Fox, Rosen, & Crawford, 2009;Junco & Cotton, 2012;Kraushaar & Novak, 2010).…”
Section: H1: Unique Predictors Of Mind-wandering Ratesupporting
confidence: 88%
“…This finding is broadly consistent with a growing body of research, using more general media multitasking questionnaires, that shows that higher endorsement of media multitasking habits is associated with lower performance of computerized attention tasks (e.g., Cain et al, 2016;Moisala et al, 2016;Ophir et al, 2009). As well, students who endorse more frequent media multitasking-particularly in academic contexts-show poorer academic performance (e.g., Fox, Rosen, & Crawford, 2009;Junco & Cotton, 2012;Kraushaar & Novak, 2010).…”
Section: H1: Unique Predictors Of Mind-wandering Ratesupporting
confidence: 88%
“…The current study therefore extends previous findings on media multitasking by using a more ecologically valid attentional task with complex linguistic stimuli, and by studying not only young adults but also adolescents in a sample much larger than in most related brain imaging studies. Based on previous studies, we expected media multitasking to be associated with increased distractibility (Ophir et al, 2009) but not with benefits in multitasking performance (Alzahabi & Becker, 2013;Sanbonmatsu et al, 2013) in the current study.…”
Section: Accepted Manuscriptmentioning
confidence: 67%
“…We used the shorter version of the media multitasking questionnaire (Ophir et al, 2009) adapted by Pea et al (2012) to create a media multitasking variable for each participant. The external validity of the resulting media multitasking questionnaire is yet to be firmly established, but several independent research groups have produced comparable indices for average media multitasking activity in their sample based on this questionnaire.…”
Section: Media Multitasking Scorementioning
confidence: 99%
See 1 more Smart Citation
“…Some findings reveal that using Facebook during studying is negatively related to grade point average in school [23]. While Ophir and colleagues [24] found that people who have the ability to multitask are more susceptible to interference from irrelevant stimuli. The results suggest that Facebook use can have an impact on academic performance.…”
Section: Introductionmentioning
confidence: 99%